2018
DOI: 10.1016/j.wear.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion evaluation of hydrogenated and silicon DLC coatings on carbon steel for use in valves, pistons and pumps in oil and gas industry

Abstract: evaluation of hydrogenated and silicon DLC coatings on carbon steel for use in valves, pistons and pumps in oil and gas industry, Wear,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…For standard engine applications, diamond-like-carbon (DLC) coatings are the material of choice, due to high wear resistance, low friction and a natural inertness that prevents surface corrosion [12][13][14]. Several publications discuss the role of MoDTC in both steel and DLC systems under different testing conditions [6,7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For standard engine applications, diamond-like-carbon (DLC) coatings are the material of choice, due to high wear resistance, low friction and a natural inertness that prevents surface corrosion [12][13][14]. Several publications discuss the role of MoDTC in both steel and DLC systems under different testing conditions [6,7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DLC films have been demonstrated to work well for a wide variety of applications because of their excellent mechanical and tribological properties . Besides their high hardness, low wear rate, low friction coefficient, bio and hemocompatibility, the superior chemical inertness and high resistivity of DLC films make them promising materials as protective films in corrosive environments . At room temperature, DLC films are chemically inert to practically any solvent and are not attacked by acid, alkalis, or organic solvent …”
Section: Introductionmentioning
confidence: 99%
“…Guan et al investigated the corrosive behaviors of Cr doped DLC (a‐C:Cr) film in variable pH solutions and revealed that doping of Cr could result in good corrosion resistances due to presence of metallic chromium and chromic oxide. Moreover, there are many other studies related to tribocorrosion of various DLC films in various aggressive environments . While these studies have been of great utility, they pay much more attention to the anticorrosion performance of DLC films and the interaction effect between their corrosion and tribological behaviors, thus the dedicated tribological study in corrosive solutions for DLC films is weakened.…”
Section: Introductionmentioning
confidence: 99%
“…There were three different hip joints coated DLC reported in Ref. [4,9]: DLC-coated femoral heads against Polyethylene implanted cups (DLC-P) [6][7][8][9], DLC-coated femoral heads against metal cups (DLC-M) [5,[10][11] and DLC-coated femoral heads against metal DLC-coated cups (DLC-DLC). Actually, the material of femoral head was metal or ceramic [7].…”
Section: Introductionmentioning
confidence: 99%